Stres dan Motivasi Belajar Anak selama Pembelajaran Daring pada Masa Pandemi Covid-19 - Yulifah Salistia Budi; Zulfikar Muhammad (LPPM STIKES Guna Bangsa, 2022)
Covid 19 is a virus that can change global conditions in order to stay at home. Education and learning policies are also carried out at home, so-called home study. It is stressful for students, teachers and parents. The stress faced by students in online learning not only leaves them vulnerable to stress, but also diminishes their motivation to learn. The objective of this study was to determine the students' level of stress and motivation for online learning and to analyse the relationship between them. The method used as a cross-sectional with the last grade students of elementary school as population which is located in South Banyuwangi, the sample was taken by purposive sampling technique and it was obtained 55 students as respondents. Collection of data used in the ESSA questionnaire for stress level and questionnaire on motivation to learn. The statistical test used in this study was Spearman's Rank, which was analysed using an apparatus with ρ 0.05. The results revealed that 80% of students had no stress and 83.6% had very strong motivation to learn. Statistical analysis of rank-spearman obtained ρ value = 0.011 with ρ value of <0.05, there was a significant correlation between stress levels and learning motivation in online learning with a close correlation score was 0,341 which was categorized as low correlation closeness. Positive parenting support and support is one factor that can reduce stress and increase student motivation to learn.